2013
DOI: 10.1002/jbt.21508
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of NicotinamideN‐Methyltransferase and its Metabolite 1‐Methylnicotinamide

Abstract: Nicotinamide N-methyltransferase (NNMT, E.C. 2.1.1.1) catalyses the N-methylation of nicotinamide to 1-methylnicotinamide (MeN). We have previously shown that the ectopic expression of NNMT in SH-SY5Y human neuroblastoma cells increased adenosine triphosphate synthesis and complex I activity, effects of which were replicated by the addition of MeN. In this study, we investigated whether NNMT expression in SH-SY5Y conferred protection against mitotoxicity induced by rotenone, potassium cyanide (KCN), 2,4-dinitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…As to how NNMT-V5 induced SirT expression is unclear. It is possible that MeN, the metabolic product of NNMT N-methylation of nicotinamide, may be responsible, which is supported by our previous studies that demonstrated that MeN increased CxI activity and cellular ATP content in SH-SY5Y cells [10,11]. In accord with this, Xie et al [33] reported that increased MeN production was responsible for the NNMTmediated increase in cellular ATP content in human colorectal cancer cells.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
See 4 more Smart Citations
“…As to how NNMT-V5 induced SirT expression is unclear. It is possible that MeN, the metabolic product of NNMT N-methylation of nicotinamide, may be responsible, which is supported by our previous studies that demonstrated that MeN increased CxI activity and cellular ATP content in SH-SY5Y cells [10,11]. In accord with this, Xie et al [33] reported that increased MeN production was responsible for the NNMTmediated increase in cellular ATP content in human colorectal cancer cells.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
“…This increase in CxI activity resulted in a subsequent increase in ATP synthesis [10] and protection against a range of mitotoxins [10,11]. The increase in CxI activity observed was mediated via a reduction in the degradation of the NDUFS3 30kDa subunit of CxI [10].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations